Evaluasi Tingkat Kematangan Teknologi Informasi Menggunakan Framework COBIT 4.1 Domain Plan and Organise dan Monitor and Evaluate pada Dinas Komunikasi dan Informatika Kota Malang - Marisania Pramesti Cahyani; Suprapto Suprapto; Aditya Rachmadi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Dinas Komunikasi dan Informatika (DISKOMINFO) kota Malang is one of the government agencies that apply information technology to support the information processing processes that it carries out. In order for the information processing to go according to expectations, IT governance is needed that is good and in line with the objectives of the relevant agencies. Based on the results of interviews conducted, several problems were found in the implementation, such as the implementation of the SOPs had not been carried out maximally, some personnel were still carrying out duties from other personnel, lack of technical personnel, MONEV activities do not run optimally and are carried out informally. Some of theses problems can be classified into processes in the Plan and Organise and Monitor and Evaluate domains in the COBIT 4.1 framework. COBIT 4.1 is used to determine the level of IT maturity and also provide recommendations form the evaluation acivities carried out. Evaluation results show, in the PO domain the average value of maturity is 2.6 or reaches level 3 (Defined Porcess, while in the ME domain the average maturity level is 2.25 or reaches level 2 (Repeatable but intuitive. Recommendations are given eith the aim that DISKOMINFO kota Malang can increase the value of IT maturity, so that existing forms of IT governance can be improved.